Analisis Implementasi Kebijakan Pelaporan Pajak Tahunan Wajib Pajak Orang Pribadi Karyawan Dengan Menggunakan E-SPT Dalam Upaya Meningkatkan Kepatuhan Wajib Pajak Di KPP Pratama Cikarang Selatan - Achmad Barlian; Nur Haeni (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
E-SPT application or referred to as electronic SPT is an application made by the Directorate General of Taxes, Ministry of Finance to be used by taxpayers for convenience in submitting SPT. The purpose of this study was to determine and analyze the implementation of the Annual Tax Reporting Policy for Individual Employee Taxpayers Using E-SPT in an Effort to Improve Taxpayer Compliance at South Cikarang Small Tax Office. This study uses a descriptive qualitative research method. Research data collection is by Observation, Interview and Documentation. The location in this study is the South Cikarang Primary Tax Service Office. The results of this study are the implementation of the Annual Tax Reporting Policy of Individual Employee Taxpayers Using E-SPT in an Effort to Increase Taxpayer Compliance at the South Cikarang Small Tax Office in 2019-2020 has not been going well as evidenced by the low ratio of taxpayer compliance in reporting The SPT is 61% in 2019 and 88% in 2020. In addition, one of the indicators in the implementation dimension is not fulfilled, namely the number of taxpayers who do not understand their tax obligations. In this study, it is known that there are several obstacles that affect the process of implementing the E-SPT, namely the lack of knowledge of taxpayers, lack of socialization of the E-SPT, errors in filling out the form and instability of the E-SPT application server, ignorance of the processes and procedures in the use of this E-SPT